Mr Muddle - Hargreaves, Roger (World International Publishing Limited, 1976)
Mr. Muddle always gets his chores wrong, so that he puts his coat on backwards and wears shoes on his hands, but his neighbor George discovers a way to get him to do things correctly.
Keywords: Juvenile literature-Fiction